(untitled) (Dike - Rivista di Storia del Diritto Greco ed Ellenistico, 2025)
Procedural penalties intended to discourage parties from engaging in lawsuits were not uncommon in ancient legal systems. In Roman law, the procedural penalty of litiscrescence was used to sanction a defendant who denied a special obligation by increasing the lis (value of the claim). As such, if the iudex (judge) sided with the plaintiff, a condemnatio in duplum had to occur. In order to prevent a condemnatio in duplum, the defendant had to acknowledge his obligation before the praetor, meaning no trial before a iudex would be needed. This article examines whether a functional analogon of the procedural penalty of litiscrescence existed in the law of Gortyn. For this, it is necessary to exegetically analyse provisions of the law of Gortyn that indicate or refer to a condemnation for the double value. Furthermore, particular attention must be given to how a confession or denial before court was handled under the law of Gortyn.